ELECTROCHEMICAL AND CORROSIVE PROPERTIES OF MICROCRISTALLIC ZINC–LEAD ALLOY (Proceedings of the YSU B: Chemical and Biological Sciences, 2007)
The electrochemical and corrosive properties of zinc-lead anodic alloy obtained by high-speed melt-hardening method with application of direct current has been investigated in this paper. This alloy permits to apply for anodes of dry alkaline batteries.
Keywords: zinc-lead anodic alloy; high-speed melt-hardening method